Follicular Eruption With Folliculotropic Lymphocytic Infiltrates Associated With Iatrogenic Immunosuppression: Report and Study of 3 Cases, and Review of the Literature. (July 2020) - Avitan-Hersh, Emily; Dias-Polak, David; Ramon, Michal; Sahar, Dvora; Magen, Daniella; Pollack, Shirley; Bergman, Reuven
Abstract : Background: Several cases of folliculotropic mycosis fungoides, associated with immunosuppressive therapy, including calcineurin inhibitors, have been reported in solid organ transplant patients. We have encountered 3 patients on immunosuppressive therapy who developed follicular eruptions with folliculocentric infiltrates of nonatypical lymphocytes. Objective: To characterize these follicular eruptions and review the literature. Methods: Three patients, aged 7–15 years, who were treated with systemic immunosuppressive therapy developed follicular eruptions characterized histopathologically by folliculocentric lymphocytic infiltrates. These were studied clinically, histopathologically, immunophenotypically, and molecularly for T-cell receptor (TCR) gene rearrangement. Results: All 3 cases were characterized histopathologically by folliculocentric infiltrates of nonatypical CD3 + T lymphocytes with variable follicular exocytosis. Two cases also showed follicular mucinosis. Marked reduction in CD7 + staining, and marked predominance of CD4 + cells over CD8 + cells was observed in all 3 cases. The TCR gene rearrangement studies were monoclonal in 2 cases. Oral calcineurin inhibitors (2 cyclosporine A and 1 tacrolimus) were part of the therapeutic regimen in all 3 patients. Their cessation along with local corticosteroid creams in 2 patients, and phototherapy with oral acitretin in one patient, was associated with complete clinical remission. Conclusions: Patients undergoing systemic immunosuppressive therapy that includes calcineurin inhibitors might develop follicular eruption with some immunophenotypical variations and a monoclonal TCR gene rearrangement but lack sufficient cytomorphological features of folliculotropic mycosis fungoides. Altering the immunosuppressive agent including calcineurin inhibitors may result in regression of the eruptions.